The Association Between Asymptomatic Bacteriuria and Any Specific Uropathogen with Renal Function and Glomerular Filtration Rate in Women of Reproductive and Postmenopausal Age: A Preliminary Study - Haghighi, Mehrdad; Behrouzmanesh , Fatemeh; Goudarzi, Mehdi (Novelty in Biomedicine, 2026)
Background: In this study, we examine the association between renal function and asymptomatic bacteriuria in women of reproductive and Postmenopausal age. Materials and Methods: This cross-sectional study was performed during 2 years (2022-2023) in Tehran, Iran. One hundred eighty-eight women of reproductive and Postmenopausal age with and without asymptomatic bacteriuria were enrolled in our study. The estimated glomerular filtration rate of all participants was evaluated. The association between reduced estimated glomerular filtration rate and asymptomatic bacteriuria was assessed, and the correlation between specific uropathogens and estimated glomerular filtration rate was analysed accordingly. Results: The mean level of creatinine in all culture-positive samples (including E. coli and non-E. coli positive samples) was 0.85 mg/dl. At the same time, it was 0.77 mg/dL in culture-negative samples (P value < 0.05). The mean eGFR was 84.65 mL/min/1.73 m2 and 101.06 mL/min/1.73 m2 in culture-positive and culture-negative urine samples, respectively (P value < 0.05). Conclusion: The estimated glomerular filtration rate was significantly lower in the culture-positive group, indicating a meaningful correlation between estimated glomerular filtration rate and asymptomatic bacteriuria. The blood urea nitrogen levels, however, were almost equal across the two culture result groups, indicating no meaningful correlation between blood urea nitrogen and asymptomatic bacteriuria. When comparing the etiologies of infection (E. coli vs. other bacterial culprits), there was no significant difference in estimated glomerular filtration rate between culture-positive patients.